Penggantian Sebagian Ransum Komersial dengan Polar dan Aditif Duck mix terhadap Komposisi Fisik Karkas Itik - Ni Wayan Siti; I.G.L.O. Cakra; K. A. Wiyana; A.T. Umiarti (Agricultural Faculty, 2009)
The substitution a part of commercial feed with pollard and duck mix additive on duck carcass physic compositionABSTRACT. The aim of this experiment was to study pollard optimum levels with additive complex mineral vitamin on the carcass physic composition Balinese male duck age 10 weeks, was carried out at Jl. Binginambe, Kediri village, Tabanan Regency. The design which used in this experiment a completely randomized design Those four treatments were ration contain 100% commercial feed (A); ration with 85% commercial feed + 15% pollard + 0,3% duck mix (B); ration with 70% commercial feed + 30% pollard + 0,3% duck mix (C); ration with 55% commercial feed + 45% pollard + 0,3% duck mix (D), respectively. The variables which measured were carcass weight, carcass percent, and carcass physic composition. The result of this experiment showed that the substitution commercial feed with pollard from 15-45% and duck mix were not significant (P 0.05) decrease carcass percent, carcass bone percent than treatment A. Meat percent on treatment B 1.81% non significant (P0.05) increase than treatment A, but C and D treatments 2.63% and 4.87% significantly increase than treatment A. Subcutan fat on C and D treatments 6.72% and 6.67% significant lower (P 0.05) than treatment A, and D treatment 4.91% significant lower than treatment B. From the result of this experiment can be concluded that substitution pollard from 15%-45% with additive 0.3% duck mix were decrease carcass percent and bone carcass percent, but substitution pollard 30% and 45% can increase meat carcass percent and decrease fat Balinese male duck age 10 weeks.